Toward Marrow Adipocytes: Adipogenic Trajectory of the Bone Marrow Stromal Cell Lineage - Matsushita, Yuki; Ono, Wanida; Ono, Noriaki (Frontiers in Endocrinology, 2022)
Bone marrow contains precursor cells for osteoblasts and adipocytes in the stromal compartment. Bone marrow adipose tissue (BMAT) is an important constituent of the bone marrow that is particularly abundant in adults. BMAT is composed of the proximal “regulated” BMAT containing individual adipocytes interspersed within actively hematopoietic marrow, and the distal “constitutive” BMAT containing large adipocytes in the area of low hematopoiesis. Historically, bone marrow adipocytes were regarded as one of the terminal states of skeletal stem cells, which stand at the pinnacle of the lineage and possess trilineage differentiation potential into osteoblasts, chondrocytes and adipocytes. Recent single-cell RNA-sequencing studies uncover a discrete group of preadipocyte-like cells among bone marrow stromal cells (BMSCs), and recent mouse genetic lineage-tracing studies reveal that these adipocyte precursor cells possess diverse functions in homeostasis and regeneration. These adipogenic subsets of BMSCs are abundant in the central marrow space and can directly convert not only into lipid-laden adipocytes but also into skeletal stem cell-like cells and osteoblasts under regenerative conditions. It remains determined whether there are distinct adipocyte precursor cell types contributing to two types of BMATs. In this short review, we discuss the functions of the recently identified subsets of BMSCs and their trajectory toward marrow adipocytes, which is influenced by multiple modes of cell-autonomous and non-cell autonomous regulations.